Saving and Investment in the Twenty-First Century: The Great Divergence – some comments from a post-Keynesian perspective - Eckhard Hein (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
This contribution discusses the book Saving and Investment in the Twenty-First Century: The Great Divergence by . It touches upon the underlying theoretical perspectives, von Weizsäcker's neo-Austrian view and Krämer's short-run Keynesian theory, and it proposes an alternative based on post-Keynesian distribution and growth theory. It also reviews the economic policy proposals of the book with respect to government deficits and debt, as well as international coordination of current-account balances, and finds broad agreement with modern post-Keynesian proposals, with some deviation when it comes to macroeconomic policy coordination among monetary, fiscal and wage/incomes policies. It concludes that these economic policy agreements should not be taken as a surprise. The requirements of stabilising government deficits and debt, in the face of an excess of private saving over private investment at full employment, and an excess of the private desire to hold net financial assets over the private-sector supply of financial liabilities, are based on solid national income and financial accounting. They are thus compatible with different macroeconomic theories regarding long-run equilibrium and adjustments towards it.
Keywords: E12; E13; E14; E20; E43; E60; 330; saving; investment; interest rate; growth; stagnation; macroeconomic policy